2008
DOI: 10.1007/s10342-008-0214-x
|View full text |Cite
|
Sign up to set email alerts
|

Response of Quercus pyrenaica (melojo oak) to soil water deficit: a case study in Spain

Abstract: In the present study, carried out from 2004 to 2006, leaf and stem water potential and stem water content were measured in Quercus pyrenaica Willd. individuals in an experimental forested catchment located in Central Western Spain under Mediterranean subhumid conditions. These indicators of tree water status were compared with soil moisture contents measured in the same area from 0 to 1 m depth and from 0 to 2.5 m depth during the last year of the study. The objectives were to clarify the seasonal and year-to-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 36 publications
1
25
0
Order By: Relevance
“…There is evidence that in semi arid environments the ability to tap water from deeper ground layers determines the treesí water status when the top soil moisture is exhausted (David et al, 2007;Dawson, 1994;Hernández-Santana et al, 2008;Villar-Salvador et al, 1997). The high E c rates observed during the dry summer of 2009 (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…There is evidence that in semi arid environments the ability to tap water from deeper ground layers determines the treesí water status when the top soil moisture is exhausted (David et al, 2007;Dawson, 1994;Hernández-Santana et al, 2008;Villar-Salvador et al, 1997). The high E c rates observed during the dry summer of 2009 (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…Despite the relatively high annual rainfall of the study area (1000 mm), it was observed that during the summer soil moisture decreased considerably due to the Mediterranean climate conditions and elevated tree water use (Herná ndez-Santana et al, 2008a). A preliminary analysis of climate trends has shown that over the last 55 years rainfall has decreased at this site by 18%, more markedly during the summer season (26% from June to September).…”
Section: Introductionmentioning
confidence: 85%
“…From a previous study (Herná ndez-Santana et al, 2008a) it is known that this plot is representative of the experimental forested catchment. Altitude ranges between 1140 and 1450 m with a SW-NE orientation.…”
Section: Experimental Sitementioning
confidence: 99%
“…DSL characteristics and dynamic properties depend on many interrelated links among climate, soil, terrain, and vegetation (Hernández-Santana et al 2008;Li et al 2002;Vörösmarty and Moore 1991). However, the measurement of DSL indices in the field is expensive, time-consuming, and technically difficult.…”
Section: Introductionmentioning
confidence: 98%